(untitled) (World Economics and Finance Bulletin, 2024)
The theoretical basis of the formation of financial results in the cottontextile cluster is considered. The process of origination of income and expenses from enterprise activity has been studied. The trends of the added value chain in cotton-textile clusters and the level of coverage of the added value chain in cotton-textile clusters operating in Uzbekistan were analyzed.